Paraphyly of Chinese Amolops (Anura, Ranidae) and phylogenetic position of the rare Chinese frog, Amolops tormotus - Cai, Hong-Xia; Che, Jing; Pang, Jun-Feng; Zhao, Er-Mi; Zhang, Ya-Ping (Zootaxa, 2007)
In order to evaluate the five species groups of Chinese Amolops based on morphological characteristics, and to clarify the phylogenetic position of the concave-eared torrent frog Amolops tormotus, we investigated the phylogeny of Amolops by maximum parsimony, Bayesian Inference, and maximum likelihood methods using two mitochondrial DNA fragments (12S rRNA, 16S rRNA). Our results supported a sister group relationship of Amolops ricketti and Amolops hainanensis. However, the grouping of Amolops mantzorum and Amolops monticola needs to be resolved with more data. Amolops tormotus was nested in genus Odorrana. Thus, recognition of the A. tormotus group is unwarranted and A. tormotus should be referred to genus Odorrana as O. tormota. This species is the sister group of O. nasica plus O. versabilis. The new classification implies that the genus Wurana is to be considered as junior subjective synonym of Odorrana.